Underlying bone change in oral squamous cell carcinoma observed from magnetic resonance imaging and computed tomography: Potential implications for tumor aggressiveness and prognosis - Gyu-Dong Jo; Kyu-Young Oh; Jo-Eun Kim; Won-Jin Yi; Min-Suk Heo; Sam-Sun Lee; Kyung-Hoe Huh (Elsevier, 2024)
Background: /purposeIn cases where oral squamous cell carcinoma (OSCC) invades the jawbone, clinicians frequently observe abnormal attenuation on computed tomography (CT) and pathologic signal intensity (SI) on magnetic resonance (MR) imaging of the affected underlying bone marrow. This study introduced a concept of "underlying bone change" to examine its association with clinicopathological features and prognosis of OSCC, as well as its correlation with medullary invasion. Materials and methods: We enrolled 93 consecutive patients diagnosed with OSCC, who underwent mandibulectomy between 2010 and 2016. CT and MR images, along with electronic medical records, were reviewed to evaluate correlations between underlying bone changes, clinicopathological features, five-year overall survival, and medullary invasion. Results: Of the 93 patients, 69 (74.2%) exhibited underlying bone sclerosis on CT, and 74 (79.6%) displayed pathological SI on MR images. These underlying bone changes correlated with the T stage and recurrence, but not with overall survival.Medullary invasion, observed in 61 (65.6%) patients, was strongly associated with T and TNM stages and was linked to poorer overall survival.The underlying bone changes on CT and MR images were positively associated with medullary invasion; however, no significant differences were found in the occurrence of underlying bone changes between the subtypes based on the extent of medullary invasion. Conclusion: Underlying bone changes on CT and MR images can provide valuable insights into the aggressiveness of bone invasion by OSCC. Accurate interpretation of these imaging findings might be crucial for correctly delineating surgical margins and preventing the overestimation of tumor extent.